BITUMEN RESOURCES OF THE EAST SIBERIAN BASIN. (7th April 2023) - Zuodong, Liu; Blackbourn, Graham; Zhixing, Wen; Hongjun, Wang; Zhengjun, He; Feng, Ma; Xiaobing, Liu; Ruiying, Chen; Haiguang, Bian
Abstract : The so‐called East Siberian "Basin" extends over an ancient continental block, the Siberian Platform, and is made up of a number of smaller‐scale basement arches and basins with a variable sedimentary cover of mostly Proterozoic and Palaeozoic ages. The basin hosts the oldest large‐scale petroleum systems known. Proterozoic ("Riphean": 1650‐650 Ma) marine source rocks, which were deposited on the passive margins which surrounded much of the Platform, generated hydrocarbons as they were buried, folded and thermally matured during a series of mostly Late Proterozoic to Cambrian continental collisions, with the final collision taking place in the Early Cretaceous along the northeastern (Verkhoyan) margin. The hydrocarbons were transported by long‐distance migration to reservoirs in the sedimentary successions which drape basement uplifts, there forming giant oil and gas accumulations which were sealed by extensive Cambrian evaporites. Subsequent uplift and unroofing, especially in the north and east of the Platform where the seal is not present, led to degradation of the oil to leave giant accumulations of bitumen, defined here as petroleum with an API gravity of less than 10° which is immobile under reservoir conditions. A significantly younger petroleum system, which may still be active, is present in the Vilyui Basin in the NE of the Siberian Platform. This basin was initiated as a mid‐Devonian rift and has a later Palaeozoic and Mesozoic fill. Bitumen accumulations in the East Siberian Basin occur mainly in Precambrian, Cambrian and Permian reservoir rocks, and began to form from precursor oils during the Permian. Around twenty‐five named fields have been described, many of which comprise portions of more extensive belts of bitumen occurrence. Although geological mapping of natural resources in the East Siberian Basin has been carried out since the 19th century, the region remains under‐explored and none of the bitumen accumulations has yet been developed. An attempt is made in this paper to catalogue and map all recorded occurrences of bitumen throughout the East Siberian Basin. Regional geological studies have been conducted in order to understand the origin and habitat of each occurrence. So far as possible, data on the areal extent and stratigraphic thickness of each bitumen occurrence has been collated, together with data on bitumen saturations and quality. These data were used to calculate resource volumes for each accumulation from first principles. Thus the total bitumen resources within the East Siberian Basin have been calculated as 24, 640 MM (million) tonnes. Disregarding accumulations regarded as either of insufficient resource‐density or too small to merit consideration, this figure has been reduced to 14, 760 MM tonnes. Recoverable reserves, by analogy with comparable resources worldwide, are calculated as 6100 MM tonnes (approximately 33, 900 MM brl)